2015
DOI: 10.5539/ijbm.v10n3p279
|View full text |Cite
|
Sign up to set email alerts
|

Mergers and Acquisitions in Banking: A Framework for Effective IT Integration

Abstract: This study aims to identify key issues in the information technology (IT) integration in mergers and acquisitions (M&A) in banking and propose an approach to increase the efficiency of such integration. The study produces a first cut IT integration framework based on the literature review into the key factors in IT integration in banking and selected popular IT governance models, such as Control Objectives for Information and related Technology (COBIT), and then refines it with the help of IT practitioners bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…absorption vs "best of breed") and the dynamics of the IT integration process. Kovela and Skok (2015), suggests that considering the pervasiveness of the IT function in banking business operations it would make sense to consider the post-merger IT integration project in the context of IT governance. Kovela and Skok propose structuring the IT integration process based on the elements of Control Objectives for Information and Related Technologies (COBIT), a popular IT governance framework by ISACA ( 2018), and combine it with the reflections of selected leading industry practitioners based on their involvement in a diverse selection of high-profile banking M&A projects.…”
Section: Academic Theory-basedmentioning
confidence: 99%
See 2 more Smart Citations
“…absorption vs "best of breed") and the dynamics of the IT integration process. Kovela and Skok (2015), suggests that considering the pervasiveness of the IT function in banking business operations it would make sense to consider the post-merger IT integration project in the context of IT governance. Kovela and Skok propose structuring the IT integration process based on the elements of Control Objectives for Information and Related Technologies (COBIT), a popular IT governance framework by ISACA ( 2018), and combine it with the reflections of selected leading industry practitioners based on their involvement in a diverse selection of high-profile banking M&A projects.…”
Section: Academic Theory-basedmentioning
confidence: 99%
“…The academic sources view the post-merger IT integration chiefly in the context of business-IT alignment, IT governance, and specific aspects such as systems, process, knowledge, and risk. Reflecting on this situation and based on an earlier work by one of the authors (Kovela & Skok, 2015), several applicable popular industry frameworks were identified (see Table 3).…”
Section: Industry Standards and Frameworkmentioning
confidence: 99%
See 1 more Smart Citation